Motivation, a determining factor in making the reading-writing process more effective - Sepúlveda, Yazmin; Adriana Roa, Yazmin; Milena Salazar, Sandra (Rastros Rostros, 2023)
Writing is an excellent intellectual exercise in which one learns to structure ideas and thoughts clearly. This definition was the fundamental basis for the realization of each of the workshops developed in the action plan of this research.